A comparative bibliography of the sheets and publishers' cloth cases of the demy octavo works of Charles Dickens, 1837-1872 - Kremers, Lars Hendrikus (Curtin University, 2013)
This thesis sought to fill a gap in the bibliography of Charles Dickens. The research reported is focused on the twelve demy octavo works (the original form that carried most of his major novels) published during the period, 1837-1872; detailing the various printings of their sheets and the cloth cases provided for them. This represents the first substantial study into the primary and later varieties of cloth provided for Dickens’s demy octavo works.